New Opportunities for Diagnosis and Prognosis of Stroke: The Benefits of Across Border Approaches - Vivien, Denis (Hämostaseologie, 2021)
Ischemic stroke is a leading cause of disability, with its treatment not yet optimal. It is thus mandatory to make preclinical research on this topic more efficient. This review summarizes current development of research aimed to improve diagnosis and prognosis of ischemic stroke. For more details, see our recent review published in Lancet Neurology.
Keywords: stroke/prevention; imaging; animal models; proteases